Welfare state futures - Bonoli, Giuliano; Leibfried, Stephan (New York : Cambridge University Press, 2001)
The welfare state is in hard times, according to today's consensus. The deterioration of exceptional economic performance - the basis for the 'Golden Age' of welfare capitalism - seems irreversible: this has slowed down welfare state expansion and radically shifted the ground for discussion on the future of the welfare state. This volume takes stock of 'the state of the welfare state': How can we build a theory of the welfare state? How did the post-World War II welfare state relate to economic development? How do welfare states change? How did the reforms of pension systems - a key welfare state sector - develop in OECD countries? How did the most developed 'Nordic welfare state' fare? How viable are today's advanced welfare states in the international economy? How may we recast the European welfare states for the twenty-first century?
1. Welfare state futures. An introduction / Stephan Leibfried and Herbert Obinger -- 2. Towards a theory of the welfare state / Franz-Xaver Kaufmann -- 3. The dog that didn't bark: economic development and the postwar welfare state / Francis G. Castles -- 4. How do welfare states change? Institutions and their impact on the politics of welfare state reform in Western Europe / Giulano Bonoli and Bruno Palier -- 5. Elephants on the move. Patterns of public pension reform in OECD countries / Karl Hinrichs -- 6. The Nordic welfare state in a European context: dealing with new economic and ideological challenges in the 1990s / Stein Kuhnle -- 7. The viability of advanced welfare states in the international economy. Vulnerabilities and options / Fritz W. Scharpf -- 8. Recasting European welfare states for the 21st century / Maurizio Ferrera, Anton Hemerijck and Martin Rhodes.
Includes bibliographical references and index.
Keywords: Welfare state